(untitled) (Journal of Economic Additions, 2026)
This study seeks to distinguish between creative accounting and accounting fraud by identifying their motives and indicators in the Algerian context, using case studies of an industrial and a commercial company based on auditor interviews. Results indicate that external pressures to enhance corporate image drive creative accounting through exploiting flexibility in standards, while internal tax pressures lead to fraud involving clear violations. The main distinction lies in management’s strategic intent. The study proposes a framework for differentiation and underscores the need for stronger internal controls, ethical practices, and tighter regulations to reduce manipulation. Jel Classification Codes: M40, M41, K42.